2015
DOI: 10.2217/fon.15.101
|View full text |Cite
|
Sign up to set email alerts
|

miRNA-15a/16: As Tumor Suppressors and More

Abstract: Since their first discovery in chronic lymphocytic leukemia, miR-15a and miR-16 have been reported to act as tumor suppressors or potential oncomiRs in different types of cancer. This review summarizes the history, biological properties and the important functions of these two miRNAs in cancer. It also introduces their roles as regulators of immune responses and angiogenesis, endogenous controls as well as potential targets and hallmarks of cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
62
2
3

Year Published

2016
2016
2021
2021

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 75 publications
(68 citation statements)
references
References 65 publications
1
62
2
3
Order By: Relevance
“…The function of miR-16 has been primarily investigated in the field of oncology, and has been demonstrated to act as a tumor suppressor, an oncomiR (an miRNA associated with cancer), a modulator of the immune response and a negative regulator of angiogenesis (18). It has also been reported that miR-16 promotes α-synuclein aggregation by downregulating heat shock protein 70 (HSP70) in a neuroblastoma cell line (19).…”
Section: Discussionmentioning
confidence: 99%
“…The function of miR-16 has been primarily investigated in the field of oncology, and has been demonstrated to act as a tumor suppressor, an oncomiR (an miRNA associated with cancer), a modulator of the immune response and a negative regulator of angiogenesis (18). It has also been reported that miR-16 promotes α-synuclein aggregation by downregulating heat shock protein 70 (HSP70) in a neuroblastoma cell line (19).…”
Section: Discussionmentioning
confidence: 99%
“…In oncological studies, a growing number of miRNAs have been confirmed to have an association with a large number of neoplasms (911). For example, miR-15a and miR-16 may be closely associated with cancer pathogenesis (12,13). miR-143, as a tumor suppressor, inhibits the growth, and induces apoptosis of, gastric cancer cells through targeting cyclooxygenase-2 (14).…”
Section: Introductionmentioning
confidence: 99%
“…It is frequently downregulated and plays a crucial role in oncogenesis, including the association with lower proliferation, invasion, and metastatic potential [24]. In glioma, the expression of miR-16 is low and negatively correlates with malignancy; meanwhile, restoration of miR-16 activity can significantly inhibit glioma cell growth and invasion [15].…”
Section: Discussionmentioning
confidence: 99%